2020
DOI: 10.1103/physrevapplied.14.014074
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Thermal Near Field Through Compensation in Hyperbolic Waveguides

Abstract: A promising method to leverage near-field power densities without the use of nanoscale vacuum gaps is through hyperbolic metamaterial (HMM) waveguides. When placed between a hot and cold reservoir, an ideal HMM can transmit surface waves across several microns, enabling an extension of near-field enhancements. However, when accounting for transmission loss due to realistic levels of absorption within the waveguide, previous studies have shown that the enhancements are significantly curtailed at wide separation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To overcome this limitation, we seek a solution from the emerging theory of three-body NFRHT, which exhibits more abundant and novel physical phenomena compared to the classic two-body system, 28 due to the complexity of the heat transfer mechanism. [29][30][31] Messina and Antezza derived an expression for the near-field radiative heat flux of a three-body system in a thermal environment. 32 Based on this theory, an amplifier for photon heat tunneling was found based on a passive relay system.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, we seek a solution from the emerging theory of three-body NFRHT, which exhibits more abundant and novel physical phenomena compared to the classic two-body system, 28 due to the complexity of the heat transfer mechanism. [29][30][31] Messina and Antezza derived an expression for the near-field radiative heat flux of a three-body system in a thermal environment. 32 Based on this theory, an amplifier for photon heat tunneling was found based on a passive relay system.…”
Section: Introductionmentioning
confidence: 99%
“…Since the hybrid effect can optimize the optical performance of the system, continuous efforts have been devoted to exploring the influence of the hybridization between polaritons on heat transfer. Typically, one valuable strategy relies on the hybrid effect between the isotropic SPPs and the hyperbolic modes of the uniaxial hyperbolic substrate. Approaches based on this idea have produced remarkable research progress in improving NFRHT. For instance, Liu et al found a perfect photon tunneling with near-unity probability across the broad frequency and k -space region on the basis of the hybridization of graphene plasmons and hyperbolic modes. However, fundamental studies for the hybrid effect of the uniaxial hyperbolic substrate on anisotropic surface polaritons have so far remained elusive, especially in the field of thermal radiation.…”
Section: Introductionmentioning
confidence: 99%